Women and the Use of Public Transport in Nigerian Traditional City- Ibadan (Global Journal of Human-Social Science, 2012)
It is disheartening to note that the mobility gap between women and men has continued to widen while poverty horizon of most women continue to deepen as a result of inadequate spatial interactions The study examines the interplay between women and public transport system in Nigerian traditional city-Ibadan A purposive sampling technique was used to administered 203 questionnaires Data collected were analyzed using simple descriptive technique and correlation analysis Results reveal that public transport system in the city is inefficient The analysis also reveals that inadequate public transport system has significant impact on the livelihoods of women Findings made it clear that socio-economic variables and operational characteristics are determining factors for the patronage of public transport Based on findings and analysis the paper discussed the need for considering the mobility needs of passengers and emphasised the need for a sustainable public transport and gender planning and analysis in Nigerian public transport planning and management it also stressed that gendered-based transportation planning and management need to be examined if the reproductive and productivity roles of women in our society are to be achieved
Keywords: Gender; Public transport; Poverty; Livelihoods; Policy